Reliability of C-reactive protein as a predictor of early neurological deficit in acute ischemic stroke: is it only to be blamed? a retrospective observational study - Bansal, Vikasdeep; Agrawal, Komal (International Journal of Research in Medical Sciences, 2020)
Background: Ischemic Stroke is a common cause of morbidity and mortality. Various parameters, both clinical and laboratory have been studied as markers of Early Neurological Deterioration (END) out of which CRP has been the most important. This retrospective study of ours is an attempt to study its influence on END by minimizing other variables as much as possible. Methods: 50 patients were chosen retrospectively strictly according to laid down inclusion and exclusion criteria, their data recorded and analyzed with 17.0 SPSS software. Any p value <0.05 was taken as significant. Results: Significantly raised CRP values were found in elderly patients (p=0.0001) and in males (p=0.003). Higher incidences of ENDs were also found in elderly patients (p=0.326) and males (p=0.846) and patients with raised CRP levels (p=0.057). Conclusions: Higher Values of CRP are associated with increased frequency of ENDs. But in patients with multiple factors which can influence both CRP and END, CRP alone should not be thought of as the only culprit.